Report of the 33rd Japanese Antarctic Research ExpeditionーActivities of the summer party(1991-1992)and wintering party(1992)ー - Mitsuo Fukuchi; Masashi Sano (National Institute of Polar Research, 1996)
Summer activities in the 1991/92 austral summer and winter activities in 1992 of the 33rd Japanese Antarctic Research Expedition (JARE) are described. The JARE-33 consisted of 16 members of the summer party and 37 members of the wintering party (one member of the wintering party returned with the summer party). Two Brazilian fish physiologists joined the summer party based on the exchange scientist program of the Antarctic Treaty. The icebreaker SHIRASE left Tokyo on 14 November 1991 and arrived at Breid Bay on 18 December, where the closing of Asuka Camp was completed. Then she headed to Syowa Station and arrived there on 4 January 1992. Transportation of cargo by helicopter to Syowa Station was carried out between 23 December 1991 and 18 January 1992. A total of 848t of cargo, including pipe transport of light oil (342kl) and freight by oversnow vehicles (215t), were transported. A new central building was constructed from 23 December to 17 February as the start of an 8-year reintegration project of Syowa Station. Three generator engines of 200kVA capacity were overhauled. Concurrently, various research programs such as absolute gravity measurement and field surveys including inland oversnow traverse were performed. However, there were some problems with a super conducting gravity meter while the gravity meter was being tested for winter operation. Therefore, one scientist working on the gravity meter who planned to winter-over decided to leave Syowa Station with the gravity meter. all of the summer party left Syowa Station on 17 February and headed to Sydney, Australia, while oceanographic and marine biological observations were carried out on board. Members of the summer party of JARE-33 and the wintering party of JARE-32 returned to Narita by air on 27 March 1992. The wintering party of JARE-33 worked at Syowa Station from 1 February 1992 to 31 January 1993. The scientific research programs cover the following four major disciplines : (1) upper atmosphere physics-ground-based observations of disturbance and ...